ENVIRONMENTAL PROTECTION: FORMATION OF A RESPONSIBLE ATTITUDE TOWARDS THE ENVIRONMENT AMONG YOUTH - Burkhonjonova Dilnura Narimon qizi (International Scientific and Current Research Conferences, 2025)
This article aims to analyze the level of environmental awareness among school students in Uzbekistan and to identify effective methods for its development. The study is based on a survey conducted among students of the Presidential School. The results show that while students are aware of environmental issues, their practical involvement remains limited. The authors argue for the integration of environmental education as an essential component of the school system.